Regulating the crypto economy : business transformations and financialisation - Chiu, Iris H-Y Chiu (London, England : Zed Books, 2021)
"This book focuses on the building of a crypto economy as an alternative economic space and discusses how the crypto economy should be governed. The crypto economy is examined in its productive and financialised aspects, in order to distil the need for governance in this economic space. The author argues that it is imperative for regulatory policy to develop the economic governance of the blockchain-based business model, in order to facilitate economic mobilisation and wealth creation. The regulatory framework should cater for a new and unique enterprise organisational law and the fund-raising and financing of blockchain-based development projects. Such a regulatory framework is crucially enabling in nature and consistent with the tenets of regulatory capitalism. Further, the book acknowledges the rising importance of private monetary orders in the crypto economy and native payment systems that do not rely on conventional institutions for value transfer. A regulatory blueprint is proposed for governing such monetary orders as 'commons' governance. The rise of Decentralised Finance and other financial innovations in the crypto economy are also discussed, and the book suggests a framework for regulatory consideration in this dynamic landscape in order to meet a balance of public interest objectives and private interests. By setting out a reform agenda in relation to economic and financial governance in the crypto economy, this forward-looking work argues for the extension of 'regulatory capitalism' to this perceived 'wild west' of an alternative economic space. It advances the message that an innovative regulatory agenda is needed to account for the economically disruptive and technologically transformative developments brought about by the crypto economy."--
Acknowledgments -- Table of Cases -- Table of Legislation -- 1. A Legal Mapping of the Crypto Economy and the Drivers for Institutional Change -- 2. Rise of the Productive Crypto Economy and Need for Regulation -- 3. Financial Regulators' Approaches to the Crypto Economy -- 4. Facilitating the Crypto Economy: The Law of Business Organisations and Governance -- 5. The Financing of Blockchain-Based Business Development and the Need for Regulation -- 6. Regulating the Monetary Order of the Crypto Economy -- 7. Regulating Crypto Finance 8. Upcoming Trends and Concluding Remarks -- Bibliography -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web
Keywords: Cryptocurrencies -- Law and legislation; Blockchains (Databases) -- Law and legislation; Electronic commerce -- Law and legislation; Capital markets & securities law & regulation,Commercial law,IT & Communications law,Comparative law; Electronic books